VENUGOPAL’S SELF-CONFESSION AND POETRY: वेणुगोपाल का आत्मसंघर्ष और कवि-कर्म - Shahabuddin (International Journal of Research -GRANTHAALAYAH, 2018)
English: Venugopal has a distinct identity in Hindi poetry. The atmosphere of disillusionment and the social status quo had an effect on your poem. Oriented towards Akavita. But soon you realized his regression. As a result, progressives were oriented towards the stream. The land of reality shaped beautiful dreams of the future. Your poem conveys the hopes, dreams, feelings, sensations of the common man. It also exposes the middle class weaknesses while being sympathetic towards the neglected workers and is a proponent of action against the power. It shares the golden dreams of the future, in retaliation for its oppression-exploitation-violence. It has the content of strategy and tactics for the youth taking action from the power. Sometimes it is very suggestive and expresses socio-political reality in an interesting way. Where the dialogue style is present in it, its symbolism is multidimensional. This poem also questions the role of media by taking a sarcastic pose. Hindi: वेणुगोपाल हिन्दी कविता में विशिष्ट पहचान रखते हैं। मोहभंग के वातावरण और सामाजिक यथास्थिति का आपकी कविता पर प्रभाव पड़ा। अकविता की ओर उन्मुख हुए। परंतु शीघ्र ही आपको उसकी प्रतिगामिता का बोध हुआ। परिणामस्वरूप प्रगतिशील धारा की ओर उन्मुख हुए। यथार्थ की जमीन ने भविष्य के सुन्दर-सुखद स्वप्नों को आकार दिया। आपकी कविता साधारणजन की आशाओं, स्वप्नों, अनुभूतियों, संवेदनाओं को रूपाकार देती है। यह उपेक्षितों-श्रमिकों के प्रति संवेदना रखते हुए भी मध्यवर्गीय कमजोरियों को उजागर करती है और सत्ता के विरुद्ध मोर्चेबन्द कार्रवाही की प्रस्तावक है। यह उसके दमन-शोषण-हिंसा का प्रतिकार करते हुए भी भविष्य के सुनहरे स्वप्न बाँटती है। इसमें सत्ता से मोर्चेबन्द कार्रवाही करते युवाओं हेतु रणनीति और रणकौशल की सामग्री मौजूद है। कहीं-कहीं यह बहुत विचारोत्तेजक है और सामाजिक-राजनीतिक यथार्थ को रोचक ढंग से अभिव्यक्त करती है। इसमें जहाँ संवाद-शैली मौजूद है वहीँ इसकी सांकेतिकता बहुआयामी है। यह कविता व्यंग्यात्मक मुद्रा लेकर मीडिया की भूमिका को भी प्रश्नांकित करती है।